Tiberius Claudius Dinippus and the Food Shortages in Corinth - Barry N. Danylak (Tyndale Bulletin, 2008)
The question of food shortages in Corinth in the mid-first century AD has special interest for the study of Paul’s letters to the Corinthian church. The letters are replete with food vocabulary, and give special attention to several food related issues within the community. A number of recent scholars have proposed that the reference to ‘the present distress’ (τὴν ἐνεστῶσαν ἀνάγκην) in 1 Corinthians 7:26 is a reference to a food shortage occurring in Corinth around the time of Paul’s visit to the city in AD 51. This paper aims to examine all the available epigraphic evidence for the office of curator of the grain supply (curator annonae) in Corinth, and those who served in the office. Special attention will be given to reconstructing the career of Tiberius Claudius Dinippus, who served as curator in the mid-first century, to reassess when and how long he probably served the office. The study confirms that there was a longstanding recurring pattern of food shortage in the city; such a crisis was especially acute in the period around AD 51, when Paul had contact with the city.